WBP1L, a transmembrane adaptor protein involved in the regulation of hematopoiesis, is controlled by CRL1β-TrCP ubiquitin ligases - Duric, Iris; Krayem, Imtissal; Brdicka, Tomas (Biochemical and biophysical research communications, 2025)
WBP1L is a broadly expressed transmembrane adaptor protein involved in regulating hematopoietic stem cell function and T cell development. It interacts with NEDD4-family E3 ubiquitin ligases and regulates important chemokine receptor CXCR4. Using tandem affinity purification coupled with mass spectrometry, we identified novel WBP1L interactions with the IFNγ receptor and the Cullin-RING ubiquitin ligases CRL1β-TrCP1/2. We found that WBP1L interaction with the IFNγ receptor serves to downregulate proximal IFNγ receptor signaling in female macrophages, while the interaction with CRL1β-TrCP1/2 ubiquitin ligases regulates WBP1L protein levels. Disrupting this interaction, as well as inhibiting proteasome activity or neddylation, increased WBP1L protein levels, demonstrating that CRL1β-TrCP1/2 ubiquitin ligases regulate WBP1L protein abundance. These data provide important insights into the mechanisms controlling WBP1L function.
Keywords: Membrane adaptor proteins; membránové proteiny; signální transdukce; proteiny s repetitivními sekvencemi beta-transducinu; Membrane Proteins; HEK293 Cells; hematopoéza; adaptorové proteiny signální transdukční; Signal Transduction; Mice; NEDD4-Family ubiquitin ligases; ubikvitinligasy; Cullin-RING ubiquitin ligases; Interferon gamma receptor; Macrophages; Ubiquitin-Protein Ligases; ženské pohlaví; zvířata; HEK293 buňky; Humans; Adaptor Proteins, Signal Transducing; myši; makrofágy; Hematopoiesis; beta-Transducin Repeat-Containing Proteins; Female; lidé; WBP1L; Animals